Myall Creek day of justice [videorecording (DVD)] - Murphy, Paul J.; Billing, Roy; Graham, Marcus, 1963-; McMahon, Travis (Bounty Films, 2024)
Amidst the brutal frontier war, a group of colonists ruthlessly slaughtered an indigenous tribe. In a time when the law fails to recognize their humanity, can those with black blood ever hope to attain justice under white law? Myall Creek: Day of Justice is a gripping cinematic adaptation of an incredible true story that forever altered the course of a nation.